Multi-scale reduced graphene oxide / carbon nanotube / SiC composite material and preparation method thereof

By preparing multi-scale reduced graphene oxide/carbon nanotube/SiC composite materials, and building a three-dimensional porous structure and a multiphase heterogeneous interface, the problem of insufficient electromagnetic wave absorption performance of existing graphene materials is solved, and efficient electromagnetic wave absorption and mechanical performance improvement is achieved. It is suitable for fields such as electromagnetic shielding and radar stealth.

CN119697978APending Publication Date: 2025-03-25SDIC CERAMIC MATRIX COMPOSITES RES INST (XIAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411944348.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

When existing graphene is a new electromagnetic wave absorbing material, the electromagnetic wave absorption performance has limitations, the electromagnetic wave absorption efficiency is low, and the electromagnetic wave absorption capacity is insufficient in high-frequency band electromagnetic wave absorption capacity.

Method used

The preparation method of multi-scale reducing graphene oxide/carbon nanotube/SiC composite materials is adopted. By mixing reduced graphene oxide, carbon nanotube and silicon carbide particles, and through ultrasonic treatment, water bath heating, freeze-drying and high-temperature heat treatment, a three-dimensional porous structure and a multiphase heterogeneous interface are constructed to enhance the electromagnetic wave absorption performance of the material.

Benefits of technology

It realizes efficient electromagnetic wave absorption of composite materials in a wide frequency band range, improves the mechanical strength and conductive properties of the materials, has the characteristics of lightweight and high strength, and is suitable for electromagnetic shielding and radar stealth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119697978A_ABST
    Figure CN119697978A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material as well as a preparation method and application thereof, and belongs to the technical field of composite materials. The preparation method comprises the following steps: (1) mixing a reduced graphene oxide dispersion liquid, a carbon nanotube dispersion liquid and a silicon carbide dispersion liquid, and performing ultrasonic treatment and intermittent stirring to obtain a mixed dispersion liquid; (2) heating the mixed dispersion liquid in a water bath, and freeze-drying to obtain a dried green body; and (3) carrying out heat treatment on the dried green body to obtain the product. The silicon carbide particles, the two-dimensional reduced graphene oxide sheets and the carbon nanotubes are combined together to form a three-dimensional porous structure, the porous structure increases the propagation path of electromagnetic waves in the material, and the energy dissipation of the electromagnetic waves is improved; due to the existence of a multiphase heterogeneous interface, interface polarization loss is promoted, and the absorption efficiency of electromagnetic waves is enhanced; and a new thought and a new technical means are provided for solving the problems of electromagnetic compatibility and electromagnetic interference.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material and a preparation method thereof. Background Art

[0002] With the rapid development of information technology, the application scope of electronic equipment is becoming more and more extensive, from small portable devices in daily life to large mechanical equipment in industrial production, and the problems of electromagnetic compatibility and electromagnetic interference are becoming increasingly prominent. Especially in high-density integrated electronic systems, the radiation and interference of electromagnetic waves not only affect the normal operation of the equipment, but may also lead to problems such as information security leakage. Therefore, the development of efficient electromagnetic wave absorbing materials has become one of the important topics in the field of scientific research and technology. Traditional electromagnetic wave absorbing materials mainly include ferrites, metal powders, conductive polymers, etc., but these materials often have disadvantages such as high density, narrow absorption band, and high cost, which limits their application in the field of high-performance electromagnetic shielding and absorbing materials.

[0003] In recent years, graphene has become an ideal choice for preparing new electromagnetic wave absorbing materials due to its unique two-dimensional structure, excellent conductivity and mechanical strength. However, single graphene materials still have certain limitations in electromagnetic wave absorption performance, such as low electromagnetic wave absorption efficiency due to its thin thickness and insufficient absorption capacity in high frequency bands. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material and a preparation method thereof, so as to solve the problems of limitations in battery wave absorption performance, low electromagnetic wave absorption efficiency, and insufficient high-frequency electromagnetic wave absorption capacity when the existing graphene is used as a new type of electromagnetic wave absorption material.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] A method for preparing a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material comprises the following steps:

[0007] (1) mixing a reduced graphene oxide dispersion, a carbon nanotube dispersion and a silicon carbide dispersion, ultrasonically treating and intermittently stirring to obtain a mixed dispersion;

[0008] (2) heating the mixed dispersion obtained in step (1) in a water bath and freeze-drying to obtain a dried body;

[0009] (3) heat treating the dried green body obtained in step (2) to obtain.

[0010] The beneficial effects of the present invention are as follows: the present invention prepares a three-dimensional reduced graphene oxide / CNT / SiC composite material, in which one-dimensional silicon carbide particles are dispersed between the layers of two-dimensional reduced graphene oxide, and carbon nanotubes adhere to the surface of silicon carbide, promoting the bonding between silicon carbide particles and graphene. The experimental results show that SiC particles play a skeleton role in the 3D reduced graphene oxide / CNT / SiC composite material, providing strong support for the three-dimensional porous structure of reduced graphene oxide, and effectively avoiding the collapse of pores. In addition, the presence of carbon nanotubes not only strengthens the interface connection between SiC particles and reduced graphene oxide sheets, but also further improves the overall mechanical strength and conductive properties of the composite material. Through this unique three-dimensional porous structure and multiphase heterogeneous interface design, the 3D reduced graphene oxide / CNT / SiC composite material shows significant advantages in electromagnetic wave absorption performance. First, the porous structure increases the propagation path of electromagnetic waves inside the material and improves the energy dissipation of electromagnetic waves; secondly, the presence of multiphase heterogeneous interfaces promotes interface polarization loss and enhances the absorption efficiency of electromagnetic waves. Therefore, the composite material not only has the characteristics of light weight and high strength, but also can realize efficient electromagnetic wave absorption in a wide frequency band, and is expected to be widely used in the fields of electromagnetic shielding, radar stealth, etc. The present invention provides a new idea and technical means for solving the problems of electromagnetic compatibility and electromagnetic interference, and has important theoretical significance and practical value.

[0011] Furthermore, the reduced graphene oxide dispersion in step (1) is prepared by the following method:

[0012] First, graphite is added to concentrated sulfuric acid and stirred for the first time; then potassium permanganate is added and stirred for the second time, water bathed and diluted with water, and then hydrogen peroxide solution and dilute hydrochloric acid solution are added, and after cooling to room temperature, suction filtration is performed to obtain a solid, and finally water is added and centrifuged until the solution pH is 6-8 to obtain the product.

[0013] Furthermore, in step (1), the graphite is natural flaky graphite; the mass volume ratio of graphite to concentrated sulfuric acid is 1 g: 35-40 mL; the mass ratio of graphite to potassium permanganate is 1: 4-6; the volume ratio of the mixture obtained after the second stirring to the water added when diluting is 1: 4-6; the volume ratio of the mixture obtained after the second stirring to the hydrogen peroxide solution is 2-5: 1, and the mass concentration of the hydrogen peroxide solution is 20-30%; the volume ratio of the mixture obtained after the second stirring to the dilute hydrochloric acid solution is 2-4: 1, and the mass concentration of the dilute hydrochloric acid solution is 3-7%; and finally, water is added until the solid mass fraction is 0.8-1.2%.

[0014] Furthermore, the temperature of the first stirring is 0-4°C, and the time is 2-3h; the temperature of the second stirring is 0-4°C, and the time is 3-5h; the temperature of the water bath is 30-40°C, and the time is 3-4h.

[0015] Furthermore, in step (1), the carbon nanotubes are single-walled, double-walled or multi-walled carbon nanotubes without functional groups, with a length of 0.5-10 μm and a diameter of 4-100 nm; the concentration of carbon nanotubes in the carbon nanotube dispersion is 0.1-0.5 g / L, and the concentration of polyvinyl alcohol is 1-2 g / L; the particle size of silicon carbide particles is 5-10 μm, and the concentration of silicon carbide in the silicon carbide dispersion is 0.01-1 g / L; the mass concentration of polyvinyl pyrrolidone is 0.1-1.0%; and the mass ratio of reduced graphene oxide, carbon nanotubes and silicon carbide is 1-10:1:0.1-2.

[0016] Furthermore, in step (1), the power of the ultrasonic treatment is 500-600 W, the time is 60-80 min, and the time interval of the intermittent stirring is 10-15 min.

[0017] The beneficial effects of adopting the above further technical solution are: the present invention optimizes the internal structure of the material by controlling the material ratio and dispersion process. The two-dimensional characteristics of graphene and the one-dimensional conductivity of carbon nanotubes are combined, and the reinforcing effect of SiC particles are added to jointly construct a high-efficiency electromagnetic wave absorption and dissipation system, which not only effectively improves the electromagnetic wave absorption efficiency of the composite material, but also maintains the light weight and high strength characteristics of the material.

[0018] Furthermore, in step (2), the water bath heating temperature is 80-90° C. for 4-6 hours; and the freeze drying time is 24-36 hours.

[0019] The beneficial effect of adopting the above further technical solution is: the present invention adopts vacuum freeze-drying technology to effectively retain the three-dimensional porous structure of the material, avoiding the problem of structural collapse that may be caused by traditional drying methods.

[0020] Furthermore, in step (3), heat treatment is performed under vacuum conditions or inert gas atmosphere, the heat treatment temperature is 800-900° C., and the time is 3-4 hours.

[0021] The beneficial effect of adopting the above further technical solution is: the present invention adopts a high-temperature heat treatment method to ensure the tight bonding and excellent mechanical properties inside the material, providing a reliable guarantee for the practical application of the composite material.

[0022] A multi-scale reduced graphene oxide / carbon nanotube / SiC composite material is prepared by adopting the preparation method.

[0023] Application of the above multi-scale reduced graphene oxide / carbon nanotube / SiC composite material in the field of electromagnetic wave absorption.

[0024] The beneficial effects of the present invention are as follows: the composite material prepared by the present invention shows broad application prospects in the field of electromagnetic wave absorption. Its unique structural design and excellent performance make it an ideal choice for solving electromagnetic compatibility and electromagnetic interference problems. Whether it is electromagnetic shielding material or radar stealth technology, the composite material prepared by the present invention can play an important role and promote technological progress and development in related fields.

[0025] The present invention has the following beneficial effects:

[0026] (1) The present invention combines silicon carbide particles, two-dimensional reduced graphene oxide sheets and carbon nanotubes to form a three-dimensional porous structure, which not only effectively increases the specific surface area of ​​the material, but also provides more reflection and refraction paths for electromagnetic waves, thereby effectively improving the absorption efficiency of electromagnetic waves.

[0027] (2) The present invention uses carbon nanotubes to act as a bridge between silicon carbide particles and reduced graphene oxide, thereby enhancing the interface connection between the two and promoting interface polarization consumption, thereby further improving the electromagnetic wave absorption performance.

[0028] (3) The present invention uses lightweight reduced graphene oxide and carbon nanotubes as main components, and the use of silicon carbide ensures that the entire composite material has a lower density. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of reduced graphene oxide obtained in Example 1;

[0030] Figure 2 This is a physical picture of the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material prepared in Example 1;

[0031] Figure 3 This is a SEM image of the reduced graphene oxide / carbon nanotube composite material obtained in Comparative Example 1;

[0032] Figure 4 This is a SEM image of the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material prepared in Example 1;

[0033] Figure 5 This is a test curve of the room temperature reflectivity of the reduced graphene oxide / carbon nanotube composite material obtained in Comparative Example 1 in the 2-18 GHz frequency band;

[0034] Figure 6This is a room temperature reflectivity test curve of the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material prepared in Example 1 in the 2-18 GHz frequency band. DETAILED DESCRIPTION

[0035] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0036] Embodiment 1:

[0037] A method for preparing a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material comprises the following steps:

[0038] (1) Preparation of reduced graphene oxide dispersion

[0039] First, 1.75g ​​of natural flaky graphite was added to 65mL of concentrated sulfuric acid with a mass fraction of 98%, and stirred at 2°C for 2.5h to obtain a mixture A; then 7.5g of potassium permanganate was added to the mixture A at 2°C and stirred for 4h to obtain a mixture B; then the mixture B was placed in a water bath at 35°C for 3.5h, and deionized water was added to dilute it, the volume ratio of the mixture B to the deionized water was 1:5, and then a hydrogen peroxide solution with a mass concentration of 30% and a dilute hydrochloric acid with a mass concentration of 5% were added, the volume ratio of the mixture B to the hydrogen peroxide solution was 3.5:1, and the volume ratio of the mixture B to the dilute hydrochloric acid was 3:1. Finally, the mixture was cooled to room temperature and filtered to obtain a solid, deionized water was added to the solid mass fraction of 1.0%, and the solution was centrifuged and filtered until the pH of the solution was 7 to obtain a reduced graphene oxide dispersion. The SEM image of the reduced graphene oxide is shown in the figure Figure 1 shown.

[0040] (2) Preparation of carbon nanotube dispersion

[0041] Take 1g of single-walled carbon nanotubes (length 5μm, diameter 50nm, purity>95%) and 10g of polyvinyl alcohol, add them into 5L of deionized water, ultrasonically treat them at 550W ultrasonic power for 25min, temperature 35°C, and perform intermittent mechanical stirring at a time interval of 4min to obtain a carbon nanotube dispersion.

[0042] (3) Preparation of silicon carbide dispersion

[0043] Take 5g of silicon carbide particles (particle size of 8μm) and 5g of polyvinyl pyrrolidone and disperse them in 10L of deionized water. Ultrasonic treatment was performed at 550W ultrasonic power for 25min at a temperature of 35°C. Intermittent mechanical stirring was performed during the ultrasonic treatment at a time interval of 4min to obtain a silicon carbide dispersion.

[0044] (4) Preparation of mixed dispersion

[0045] The reduced graphene oxide dispersion, carbon nanotube dispersion and silicon carbide dispersion were mixed according to the mass ratio of reduced graphene oxide, carbon nanotube and silicon carbide being 5:1:1. During the mixing, the carbon nanotube dispersion was first added dropwise to the reduced graphene oxide dispersion and mixed evenly. Then the graphene oxide dispersion / carbon nanotube dispersion was added dropwise to the silicon carbide dispersion. The mixture was then ultrasonically treated at an ultrasonic power of 550 W for 70 min at a temperature of 35° C. Intermittent mechanical stirring was performed during the ultrasonic treatment, and the interval between mechanical stirring was 12 min.

[0046] (5) Preparation of dried green body

[0047] The mixed dispersion obtained in step (4) is subjected to vacuum freeze drying for 30 hours. During the vacuum freeze drying process, ice crystals are removed by sublimation, which does not cause the collapse of the overall structure. The three-dimensional interconnected porous structure is retained to obtain a dry body.

[0048] (6) Heat treatment

[0049] The dried body obtained in step (5) was placed in a tubular furnace for heat treatment under nitrogen protection at a temperature of 850° C. for 3.5 h to obtain a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material. Figure 2 shown.

[0050] Embodiment 2:

[0051] A method for preparing a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material comprises the following steps:

[0052] (1) Preparation of reduced graphene oxide dispersion

[0053] First, 1.75 g of natural flaky graphite was added to 61.25 mL of concentrated sulfuric acid with a mass fraction of 98%, and stirred at 2°C for 2.5 hours to obtain a mixture A; then 8.75 g of potassium permanganate was added to the mixture A at 2°C, and stirred for 4 hours to obtain a mixture B; then the mixture B was water bathed at 35°C for 3.5 hours, and deionized water was added to dilute it, and the volume ratio of the mixture B to the deionized water was 1:4, and then a hydrogen peroxide solution with a mass concentration of 30% and a dilute hydrochloric acid with a mass concentration of 5% were added, and the volume ratio of the mixture B to the hydrogen peroxide solution was 2:1, and the volume ratio of the mixture B to the dilute hydrochloric acid was 2:1. Finally, the solid was filtered after cooling to room temperature, and deionized water was added to the solid mass fraction of 1.0%. The solution was centrifuged and filtered until the pH of the solution was 7 to obtain a reduced graphene oxide dispersion.

[0054] (2) Preparation of carbon nanotube dispersion

[0055] Take 1g of single-walled carbon nanotubes (length 5μm, diameter 50nm, purity>95%) and 12g of polyvinyl alcohol, add them into 6L of deionized water, ultrasonically treat them at 550W ultrasonic power for 25min, temperature 35°C, and perform intermittent mechanical stirring at a time interval of 4min to obtain a carbon nanotube dispersion.

[0056] (3) Preparation of silicon carbide dispersion

[0057] 3 g of silicon carbide particles (particle size of 8 μm) and 4 g of polyvinyl pyrrolidone were dispersed in 1 L of deionized water, and ultrasonically treated at 550 W ultrasonic power for 25 min at a temperature of 35° C. During the ultrasonic treatment, intermittent mechanical stirring was performed at a time interval of 4 min to obtain a silicon carbide dispersion.

[0058] (4) Preparation of mixed dispersion

[0059] The reduced graphene oxide dispersion, carbon nanotube dispersion and silicon carbide dispersion were mixed according to the mass ratio of reduced graphene oxide, carbon nanotube and silicon carbide being 4:1:1. During the mixing, the carbon nanotube dispersion was first added dropwise to the reduced graphene oxide dispersion and mixed evenly. Then the graphene oxide dispersion / carbon nanotube dispersion was added dropwise to the silicon carbide dispersion. The mixture was then ultrasonically treated at an ultrasonic power of 550 W for 70 min at a temperature of 35° C. Intermittent mechanical stirring was performed during the ultrasonic treatment, and the interval between mechanical stirring was 12 min.

[0060] (5) Preparation of dried green body

[0061] The mixed dispersion obtained in step (4) is subjected to vacuum freeze drying for 30 hours. During the vacuum freeze drying process, ice crystals are removed by sublimation, which does not cause the collapse of the overall structure. The three-dimensional interconnected porous structure is retained to obtain a dry body.

[0062] (6) Heat treatment

[0063] The dried green body obtained in step (5) is placed in a tubular furnace and heat treated under nitrogen protection at a temperature of 800° C. for 3 hours to obtain a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material.

[0064] Embodiment 3:

[0065] A method for preparing a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material comprises the following steps:

[0066] (1) Preparation of reduced graphene oxide dispersion

[0067] First, 1.75 g of natural flaky graphite was added to 70 mL of concentrated sulfuric acid with a mass fraction of 98%, and stirred at 2°C for 2.5 h to obtain a mixture A; then 10.5 g of potassium permanganate was added to the mixture A at 2°C, and stirred for 4 h to obtain a mixture B; then the mixture B was placed in a water bath at 35°C for 3.5 h, and deionized water was added to dilute it, the volume ratio of the mixture B to the deionized water was 1:6, and then a hydrogen peroxide solution with a mass concentration of 30% and a dilute hydrochloric acid with a mass concentration of 5% were added, the volume ratio of the mixture B to the hydrogen peroxide solution was 5:1, and the volume ratio of the mixture B to the dilute hydrochloric acid was 4:1. Finally, the solid was filtered out after cooling to room temperature, deionized water was added to the solid mass fraction of 1.0%, and the solution was centrifuged and filtered until the pH of the solution was 7 to obtain a reduced graphene oxide dispersion.

[0068] (2) Preparation of carbon nanotube dispersion

[0069] Take 1g of single-walled carbon nanotubes (length 5μm, diameter 50nm, purity>95%) and 8g of polyvinyl alcohol, add them into 4L of deionized water, ultrasonically treat them at 550W ultrasonic power for 25min, temperature 35°C, and perform intermittent mechanical stirring at a time interval of 4min to obtain a carbon nanotube dispersion.

[0070] (3) Preparation of silicon carbide dispersion

[0071] 8 g of silicon carbide particles (particle size of 8 μm) and 6 g of polyvinyl pyrrolidone were dispersed in 1 L of deionized water, and ultrasonically treated at 550 W ultrasonic power for 25 min at a temperature of 35° C. During the ultrasonic treatment, intermittent mechanical stirring was performed at a time interval of 4 min to obtain a silicon carbide dispersion.

[0072] (4) Preparation of mixed dispersion

[0073] The reduced graphene oxide dispersion, carbon nanotube dispersion and silicon carbide dispersion were mixed according to the mass ratio of reduced graphene oxide, carbon nanotube and silicon carbide of 6:1:1. During the mixing, the carbon nanotube dispersion was first added dropwise to the reduced graphene oxide dispersion and mixed evenly. Then the graphene oxide dispersion / carbon nanotube dispersion was added dropwise to the silicon carbide dispersion. The mixture was then ultrasonically treated at an ultrasonic power of 550 W for 70 min at a temperature of 35° C. Intermittent mechanical stirring was performed during the ultrasonic treatment, and the interval between mechanical stirring was 12 min.

[0074] (5) Preparation of dried green body

[0075] The mixed dispersion obtained in step (4) is subjected to vacuum freeze drying for 30 hours. During the vacuum freeze drying process, ice crystals are removed by sublimation, which does not cause the collapse of the overall structure. The three-dimensional interconnected porous structure is retained to obtain a dry body.

[0076] (6) Heat treatment

[0077] The dried green body obtained in step (5) is placed in a tubular furnace and heat treated under nitrogen protection at a temperature of 900° C. for 3 hours to obtain a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material.

[0078] Comparative Example 1:

[0079] A method for preparing a reduced graphene oxide / carbon nanotube composite material comprises the following steps:

[0080] (1) Preparation of reduced graphene oxide dispersion

[0081] First, 1.75 g of natural flaky graphite was added to 65 mL of concentrated sulfuric acid with a mass fraction of 98%, and stirred at 2°C for 2.5 h to obtain a mixture A; then 7.5 g of potassium permanganate was added to the mixture A at 2°C, and stirred for 4 h to obtain a mixture B; then the mixture B was placed in a water bath at 35°C for 3.5 h, and deionized water was added to dilute it, the volume ratio of the mixture B to the deionized water was 1:5, and then a hydrogen peroxide solution with a mass concentration of 30% and a dilute hydrochloric acid with a mass concentration of 5% were added, the volume ratio of the mixture B to the hydrogen peroxide solution was 3.5:1, and the volume ratio of the mixture B to the dilute hydrochloric acid was 3:1. Finally, the solid was filtered out after cooling to room temperature, deionized water was added to the solid mass fraction of 1.0%, and the solution was centrifuged and filtered until the pH of the solution was 7 to obtain a reduced graphene oxide dispersion.

[0082] (2) Preparation of carbon nanotube dispersion

[0083] Take 1g of single-walled carbon nanotubes (length 5μm, diameter 50nm, purity>95%) and 10g of polyvinyl alcohol, add them into 5L of deionized water, ultrasonically treat them at 550W ultrasonic power for 25min, temperature 35°C, and perform intermittent mechanical stirring at a time interval of 4min to obtain a carbon nanotube dispersion.

[0084] (3) Preparation of mixed dispersion

[0085] The reduced graphene oxide dispersion and the carbon nanotube dispersion were mixed according to a mass ratio of reduced graphene oxide to carbon nanotube of 5:1, and ultrasonically treated for 70 min at 550 W ultrasonic power and 35° C. During the ultrasonic treatment, intermittent mechanical stirring was performed, and the interval mechanical stirring time was 12 min.

[0086] (4) Preparation of dry green body

[0087] The mixed dispersion obtained in step (3) is subjected to vacuum freeze drying for 30 hours. During the vacuum freeze drying process, ice crystals are removed by sublimation, which does not cause the collapse of the overall structure. The three-dimensional interconnected porous structure is retained to obtain a dry green body.

[0088] (5) Heat treatment

[0089] The dried green body obtained in step (4) is placed in a tubular furnace and heat treated under nitrogen protection at a temperature of 850° C. for 3.5 hours to obtain a reduced graphene oxide / carbon nanotube composite material.

[0090] Test example:

[0091] The composite materials prepared in Example 1 and Comparative Example 1 were characterized by SME and tested for room temperature reflectivity in the frequency range of 2-18 GHz using an R / T vector network analyzer.

[0092] The experimental results are as follows Figure 3-Figure 6 shown.

[0093] like Figure 3 and Figure 4 From the SEM characterization results, it can be seen that the composite material prepared in comparative document 1 presents a two-dimensional sheet structure, the surface does not have a porous structure, and the reflection and refraction path of the electromagnetic wave is single, while the composite material prepared in Example 1 of the present invention presents a three-dimensional interconnected porous structure, has a higher specific surface area, and provides more reflection and refraction paths for electromagnetic waves, effectively improving the absorption efficiency of electromagnetic waves.

[0094] like Figure 5 and Figure 6 The room temperature reflectivity test results of 2-18 GHz show that the composite material prepared in Example 1 of the present invention has a high reflectivity in the entire X-band, RL max The test value is -10.2dB (more than 90.5% of the electromagnetic waves are absorbed); RL min The test value is -20.5dB, achieving 99.1% electromagnetic wave absorption. X-band full-frequency RL ave The test value is -15.4dB, representing an average electromagnetic wave absorption efficiency greater than 97.1%. The results show that the composite material with a three-dimensional interconnected porous structure prepared by the present invention has the advantages of excellent electromagnetic wave absorption efficiency, wide absorption bandwidth, and good electromagnetic wave absorption stability.

[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a multi-scale reduced graphene oxide / carbon nanotube / SiC composite material, characterized in that: The following steps are involved: (1) mixing a reduced graphene oxide dispersion, a carbon nanotube dispersion and a silicon carbide dispersion, ultrasonically treating and intermittently stirring to obtain a mixed dispersion; (2) heating the mixed dispersion obtained in step (1) in a water bath and freeze-drying to obtain a dried body; (3) heat treating the dried green body obtained in step (2) to obtain.

2. The method for preparing the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material according to claim 1, characterized in that: The reduced graphene oxide dispersion in step (1) is prepared by the following method: First, graphite is added to concentrated sulfuric acid and stirred for the first time; then potassium permanganate is added and stirred for the second time, water bathed and diluted with water, and then hydrogen peroxide solution and dilute hydrochloric acid solution are added, and after cooling to room temperature, suction filtration is performed to obtain a solid, and finally water is added and centrifuged until the solution pH is 6-8 to obtain the product.

3. The method for preparing the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material according to claim 2, characterized in that: In the step (1), the graphite is natural flaky graphite; the mass volume ratio of graphite to concentrated sulfuric acid is 1 g: 35-40 mL; the mass ratio of graphite to potassium permanganate is 1: 5-6; the volume ratio of the mixture obtained after the second stirring to the water added when diluting is 1: 4-6; the volume ratio of the mixture obtained after the second stirring to the hydrogen peroxide solution is 2-5: 1, and the mass concentration of the hydrogen peroxide solution is 20-30%; the volume ratio of the mixture obtained after the second stirring to the dilute hydrochloric acid solution is 2-4: 1, and the mass concentration of the dilute hydrochloric acid solution is 3-7%; and finally, water is added until the solid mass fraction is 0.8-1.2%.

4. The method for preparing the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material according to claim 2, characterized in that: The temperature of the first stirring is 0-4°C, and the time is 2-3h; the temperature of the second stirring is 0-4°C, and the time is 3-5h; the temperature of the water bath is 30-40°C, and the time is 3-4h.

5. The method for preparing the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material according to claim 1, characterized in that: In the step (1), the carbon nanotubes are single-walled, double-walled or multi-walled carbon nanotubes without functional groups, with a length of 0.5-10 μm and a diameter of 4-100 nm; the concentration of carbon nanotubes in the carbon nanotube dispersion is 0.1-0.5 g / L, and the concentration of polyvinyl alcohol is 1-2 g / L; the particle size of silicon carbide particles is 5-10 μm, and the concentration of silicon carbide in the silicon carbide dispersion is 0.01-1 g / L; the mass concentration of polyvinyl pyrrolidone is 0.1-1.0%; and the mass ratio of reduced graphene oxide, carbon nanotubes and silicon carbide is 1-10:1:0.1-2.

6. The method for preparing the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material according to claim 1, characterized in that: The power of the ultrasonic treatment in step (1) is 500-600 W, the time is 60-80 min, and the time interval of intermittent stirring is 10-15 min.

7. The method for preparing the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material according to claim 1, characterized in that: In the step (2), the water bath heating temperature is 80-90° C. for 4-6 hours; and the freeze drying time is 24-36 hours.

8. The method for preparing the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material according to claim 1, characterized in that: In the step (3), heat treatment is performed under vacuum conditions or inert gas atmosphere, the heat treatment temperature is 800-900° C., and the time is 3-4 hours.

9. A multi-scale reduced graphene oxide / carbon nanotube / SiC composite material, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. Application of the multi-scale reduced graphene oxide / carbon nanotube / SiC composite material according to claim 9 in the field of electromagnetic wave absorption.